Supply market uncertainty: Exploring consequences and responses within sustainability transitions. Issue 3 (September 2015) - Knight, Louise; Pfeiffer, Alexandra; Scott, James
Abstract Often it is commercial, not technological, factors which hinder the adoption of potentially valuable innovations. In energy policy, much attention is given to analysing and incentivising consumer demand for renewable energy, but new technologies may also need new supply markets, to provide products and services to build, operate and maintain the innovative technology. This paper addresses the impact of supply constraints on the long-term viability of sustainability related innovations, using the case of bioenergy from organic waste. Uncertainties in the pricing and availability of feedstock (i.e. waste) may generate market deadlock and deter potential investors. We draw on prior research to conceptualise the problem, and identify what steps might be taken to address it. We propose a research agenda aimed at purchasing and supply scholars and centred on the need to understand better the interplay between market evolution and supply uncertainty and 'market shaping' – how stakeholders can legitimately influence supply market evolution – to support the adoption of sustainability related innovation.